The parallelism in the algorithm of the synthesis of models of optimal complexity based on the genetic algorithms - Горбійчук, Михайло Іванович; Медведчук, Віра Михайлівна; Пашковський, Богдан Васильович (Eastern-European Journal of Enterprise Technologies, 2014)
An analysis of methods for constructing mathematical models has shown that one of the most promising methods for constructing such models is the inductive method of model self-organization that allows to obtain the model of optimal complexity. The disadvantage of this method is its high dimensionality, which limits the scope of this method. A method of the synthesis of models of optimal complexity based on the genetic algorithms, which has a much smaller dimensionality than the inductive method of model self-organization, can be an alternative to it. But for complex technical facilities with a large number of input variables, computing time expenditures are still quite noticeable. In order to reduce such expenditures, analysis of the method of constructing empirical models of optimal complexity based on the genetic algorithms of optimal complexity for parallelism by constructing the algorithm graphs was carried out. It was shown that this algorithm has an internal parallelism, which allows to develop an effective program of the algorithm implementation on a parallel-structure computer system, and this in turn would reduce the computer time expenditures at the practical implementation of the algorithm.